Contemporary Fiqh Perspective on Cryptocurrency: A Comparative Study of the Indonesian Ulema Council and Perlis State Fatwas - Irfan Affandi, Nik Fakhrul Hafiz bin; Sulistio, Dody; Rafikah; Abubakar, Ismail Yau; Muhtar, Amin (Journal of Islamic Legal Thought and Jurisprudence, 2025)
This study aims to analyze cryptocurrency fatwas issued in two countries: Malaysia and Indonesia. The objectives include identifying the fatwas related to cryptocurrency, examining the similarities and differences between the two, and understanding the reasoning behind them. The research employs a qualitative approach using library research and document analysis as data collection methods. The findings reveal two main points: First, scholars hold differing opinions on cryptocurrency some deem it impermissible (haram), while others consider it permissible (halal). Second, both Malaysia and Indonesia share a common stance in their fatwas by not recognizing cryptocurrency as legal tender or a valid means of payment, as it contradicts national regulations and monetary laws.